Nomogram based overall survival prediction in stereotactic body radiotherapy for oligo-metastatic lung disease. Issue 2 (May 2017) - Tanadini-Lang, S.; Rieber, J.; Filippi, A.R.; Fode, M.M.; Streblow, J.; Adebahr, S.; Andratschke, N.; Blanck, O.; Boda-Heggemann, J.; Duma, M.; Eble, M.J.; Ernst, I.; et al.
Abstract: Background: Radical local treatment of pulmonary metastases is practiced with increasing frequency due to acknowledgment and better understanding of oligo-metastatic disease. This study aimed to develop a nomogram predicting overall survival (OS) after stereotactic body radiotherapy (SBRT) for pulmonary metastases. Patients and methods: A multi-institutional database of 670 patients treated with SBRT for pulmonary metastases was used as training cohort. Cox regression analysis with bidirectional variable elimination was performed to identify factors to be included into the nomogram model to predict 2-year OS. The calibration rate of the nomogram was assessed by plotting the actual Kaplan–Meier 2-year OS against the nomogram predicted survival. The nomogram was externally validated using two separate monocentric databases of 145 and 92 patients treated with SBRT for pulmonary metastases. Results: The median follow up of the trainings cohort was 14.3 months, the 2-year and 5-year OS was 52.6% and 23.7%, respectively. Karnofsky performance index, type of the primary tumor, control of the primary tumor, maximum diameter of the largest treated metastasis and number of metastases (1 versus >1) were significant prognostic factors in the Cox model (all p  < 0.05). The calculated concordance-index for the nomogram was 0.73 (concordance indexes of all prognostic factors between 0.54 and 0.6). Based on the nomogram the training cohort was divided into 4 groups and 2-year OS ranged between 24.2% and 76.1% (predicted OS between 30.2% and 78.4%). The nomogram discriminated between risk groups in the two validation cohorts (concordance index 0.68 and 0.67). Conclusions: A nomogram for prediction of OS after SBRT for pulmonary metastases was generated and externally validated. This tool might be helpful for interdisciplinary discussion and evaluation of local and systemic treatment options in the oligo-metastatic setting. Key message: A nomogram for prediction of overall survival after stereotactic body radiotherapy (SBRT) for pulmonary metastases was developed and externally validated. This tool might be helpful for interdisciplinary discussion and evaluation of local and systemic treatment options in the oligo-metastatic setting.